The path to Net Zero carbon emissions for veterinary practice - Watson, Jeremy A.; Klupiec, Corinna; Bindloss, Jane; Morin, Mariane (Frontiers in Veterinary Science, 2023)
The urgent need to reduce greenhouse gas emissions in line with the Paris Agreement is a compelling reason for the entire veterinary profession to act on climate change because of its impact on animal health. The aim of this perspective is to provide a business framework that veterinary practices can use to implement the path to Net Zero carbon emissions. Practice management is identified as a key stakeholder capable of implementing significant change within the sector. Climate related business opportunities and challenges are identified and integrated into a stepwise process for practices to follow. The pathway requires establishing a culture of sustainability within the veterinary team, measuring and reporting emissions, setting targets and systematically prioritizing reductions. Practices can begin this process immediately by reducing emissions under direct control of the business (Scope 1) and emissions from electricity purchases (Scope 2). To complete the pathway, emissions from all other activities (Scope 3) will need to be reduced and offset. Reduction of Scope 3 emissions is more challenging and will require collaboration between all supply chain stakeholders. The progression of climate change is now inevitable and a proactive approach from veterinary leaders, in particular practice management, will provide new opportunities, manage risks and inspire the broader veterinary sector to join their efforts to achieve a better future for animal health.